Evaluation of the Implementation of Exclusive Breastfeeding Policy at Work in the Private Sector - Dina, Resa Ana; Yudha, Eka Purna; Pangestuti, Dina Rahayuning; Kustanti, Erin Ratna (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
Giving exclusive breastfeeding in Indonesia, especially in the workplace is still not optimal. Data from Indonesia’s Health Profile in 2016 shows that exclusive breastfeeding coverage for 6 months is 54%. Methods of this research used The Important Performance Analysis (IPA) analysis tool is used to determine the stakeholder satisfaction assessment of female worker respondents regarding the implementation of exclusive breastfeeding in the private sector. This research was conducted at selected private companies in the City and District of Semarang. Primary data were obtained from in-depth interviews with company management and filling in questionnaires by female workers. Based on the analysis of Important Performance Analysis (IPA), the assessment of workers’ attitudes towards the performance of service corner in companies/private sectors is quite good (ordinary) with a value of 63 (out of a maximum value of 102). This research concludes that the workers want the location of the breastfeeding corner close to where they work and sufficient time to express milk. Women workers also want to prepare basic infrastructure such as pumping equipment, storage bottles and refrigerators to store milking milk.